Do Political Parties Satisfy Voter's Communication Needs? Content Analysis of Twitter, YouTube and Instagram Posts - Kaur, Manpreet; Verma, Rajesh; Otoo, Frank Nana Kweku (Universitas Semarang, 2024)
Introduction: In an electronic democracy, politicians avoid being solely dependent on traditional communication channels like news media. Social media acts a political communication tool and Uses Gratification (UG) theory explains how people use media for their needs. Therefore, the attempt has been made to analyze the information shared on these social media platforms by political parties to communicate has any effect on communication needs according to Uses Gratification theory. Methods: Content analysis was employed to achieve the objectives using R software, where in data was acquired from social media platforms of major political parties of India and the coding was developed to classify the extracted data into communication needs as per UG theory. Findings: The content analysis shows that among all parties, BJP has higher visibility and consistency on Twitter and Instagram, satisfying cognitive needs. Most parties satisfy affective needs on Twitter, Instagram, and YouTube. However, YouTube content is less satisfying for personal integrative, social integrative, and tension released needs. Originality: The current study tried to use innovative methods or combining methods in a new way. It provided new insights or implications that have not been extensively discussed. Therefore, Political parties should focus on specific social media for interactive and efficient information spread.